THE INFLUENCE OF GLYCEMIA ON SHORT-TERM PROGNOSIS IN MYOCARDIAL INFARCTION WITHOUT ANAMNESIS OF 2ND TYPE DIABETES - K. K. Kholmatova; I. V. Dvoryashina; T. V. Supryadkina (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To estimate the impact of glycemia recorded during myocardial infarction (MI) in-patient care on short-term prognosis of patients without 2nd type diabetes mellitus (2DM).Material and methods. Totally 296 patients were prospectively investigated. According to glucose levels patients were divided into three groups: 1st with ≤4,0 mM/l (7,4%); 2nd with 4,01–7,79 mM/l (69,9%); 3rd with ≥7,8 mM/l (22,6%). The rate of glucose metabolism disorders and complications during in-hospital care were studied.Results. In 2/3 of patients with glycemia ≥7,8 mM/l at hospitalization, later the changes of glucose metabolism were found by glucosetolerance test: prediabetes (36,9%), 2DM (32,3%). In the patients of 3rd group significantly higher was the rate of 3-vessel disease (41,8%) anf MI complications: congestive left-ventricular failure — 52,2% vs 27,3% in the 1st group and 34,1% in the second (p=0,017), cardiogenic shock — 26,9% vs 4,5% and 6,8% (p<0,001), conduction disorders — 27,3% vs 9,1% and 11,7% (p=0,006), in-hospital mortality — 13,8% vs 4,5% and 4,4% (p=0,025). The risk of death in subjects with glycemia ≥7,8 mM/l was 3,48 (95% CI: 1,41–8,60) times higher than in normoglycemic (p=0,007). The glycemia was independently linked with complications of MI during in-hospital period: OR = 1,128; 95% CI: 1,005–1,266 (p=0,042), — as also with the age, severity of myocardial damage and systolic pressure at admittance.Conclusion. There was higher prevalence of MI complications and 3 times higher risk of death in patients without 2DM, but having ≥7,8 mM/l glucose (22,6% of patients) at admittance. The glycemia parameter was an independent predictor for unfavorable prognosis of MI without previous 2DM diagnosis and should be used as part of secondary prevention care.